Is there a difference in bony stability at three months postoperatively between opening-wedge high tibial osteotomy and opening-wedge distal tuberosity osteotomy? - Suguru Koyama; Keiji Tensho; Kazushige Yoshida; Hiroki Shimodaira; Daiki Kumaki; Yusuke Maezumi; Hiroshi Horiuchi; Jun Takahashi (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology)
Objective: To compare the initial postoperative stability of opening-wedge high tibial osteotomy (HTO) and opening-wedge distal tuberosity osteotomy (DTO) and investigate the factors that influence initial stability. Methods: Patients with the same operative indications who underwent HTO (n = 51) and DTO (n = 55) were included. Demographic and preoperative radiographic data (weight-bearing line percentage [%WBL], femoral-tibial angle [FTA], medial proximal tibial angle [MPTA], posterior tibial slope and correction angle), and postoperative computed tomography (CT) scan data (initial postoperative stability [12 weeks postoperative], and hinge fracture [1 and 12 weeks postoperatively], and hinge length, flange thickness, flange length, axial flange osteotomy angle, sagittal flange osteotomy angle [1 week postoperatively]) were statistically analyzed. As a subgroup analysis, HTO and DTO patients were divided into Stable and Unstable groups respectively based on postoperative CT at 12 weeks; demographic and radiological data were compared. Results: Patients with DTO was significantly younger (median [range]; 59 [22, 73] vs 64 [45, 75], P = 0.02) and had a smaller preoperative deformity (%WBL: median [range]; 28.9 [12.8, 46.0] vs 24.3 [4.9, 44.3], P < 0.01, FTA: median [range]; 179.0 [173.0, 183.0] vs 180.0 [172.5, 186.2], P < 0.01, MPTA: median [range]; 84.0 [79.0, 87.1] vs 83.0 [78.2, 86.5], P = 0.04) and smaller correction angles (median [range]; 9 [6, 12] vs 10 [7, 15], P < 0.01). Postoperative CT data showed that DTO was associated with significantly more unstable cases (stable/unstable: 31/24 vs. 39/12, P = 0.02) and hinge fractures (none/1/2/3: 24/25/3/3 vs. 36/12/1/2, P < 0.01) and shorter hinge (median [range]; 27.8 [14.7, 43.4] vs 32.6 [22.5, 44.0], P < 0.01) than HTO. The Unstable DTO group had significantly shorter hinges (median [range]; 23.2 [14.7, 33.9] vs 31.1 [15.2, 43.4], P < 0.01) and thicker flanges (median [range]: 15.2 [9.0, 24.8] vs. 11.0 [6.8, 13.8], P < 0.01) than the stable group. The other data were not significantly different between the two groups. Conclusion: DTO resulted in less initial postoperative stability than HTO. The risk factors for initial instability in DTO were a short hinge and thick flange.